Abstract 014: Beveled‐Tip Aspiration Catheters Reduce Stoke Procedure Time And Cost For Large And Medium Vessel Occlusions - Mohamad M. Ezzeldin; Riichi Ota; Eric Riha; Adam Delora; Bader Alenzi; Victoria Gordon; Himanshu Gupta; Rime Ezzeldin; Saif Bushnaq (Stroke: Vascular and Interventional Neurology)
Introduction Thrombectomy catheters with a unique angled‐tip design (ZoomTM Aspiration Catheters, Imperative Care Inc., Campbell, CA) have recently emerged as promising devices for treating acute ischemic stroke. The angled‐tip configuration is engineered to enhance device trackability and optimize clot engagement. Following promising initial results observed during our catheter evaluation, we integrated these novel catheters into the majority of thrombectomy procedures at our institution. In this study, we aimed to determine whether the utilization of angled‐tip catheters could lead to reduced procedural expenses and shorter time to reperfusion in our patient population. Methods We conducted a retrospective single‐center cohort study involving consecutive patients with acute ischemic stroke due to large and medium vessel occlusions. All patients were treated by a single operator between January 2020 and March 2023. Patients treated within the 18‐month period preceding the introduction of the Zoom aspiration catheters using traditional straight‐tip catheters were assigned to the straight‐tip group, while those treated with the Zoom aspiration catheters were assigned to the angled‐tip group. Our primary analysis was a cost comparison between the angled‐tip and straight‐tip groups using the list prices associated with each device employed in the procedures. The secondary analysis was focused on safety and procedural outcomes including self‐adjudicated modified Thrombolysis in Cerebral Infarction (mTICI) reperfusion scores and time from puncture to reperfusion. Frequencies were compared using the Fisher’s exact test and means were compared using a two‐sample t‐test. P‐values <0.05 were considered significant. Results A total of 163 patients were included, with 68 (41.7%) in the straight‐tip group and 95 (58.3%) in the angled‐tip group. There were no significant difference in age, sex, comorbidities, initial National Institutes of Health Stroke Scale score, access site, or procedure type between the two groups. However, utilization of the ADAPT thrombectomy technique was significantly higher in the angled‐tip group (55.9%, 38/68) compared to the straight‐tip group (13.7%, 13/95) which primarily used the Solumbra technique, p<0.001. Overall, the angled‐tip group demonstrated a significant decrease in mean procedure cost ($9,728 vs $12,127; p=0.002). Sub‐group analyses based on the procedure type showed that the angled‐tip group was associated with a numeric decrease in cost; however, due to the lower sample size statistical significance was not achieved (Table). The angled‐tip group was also associated with significantly shorter times to achieve mTICI ≥2B reperfusion (38.30 min vs 53.26 min; p=0.018), mTICI ≥2C reperfusion (45.09 min vs 58.74 min; p=0.042), and procedure completion (46.42 min vs 62.38 min; p=0.022). There were no significant differences in the overall rate of hemorrhage between the angled‐tip (17.9%) and straight‐tip groups (20.6%), p=0.690, though we did observe a numerical decrease in the rate of larger hemorrhages (HI2 and PH2) in the angled‐tip group (Table). Both groups achieve similar rates of mTICI ≥2B reperfusion. Conclusion The angled‐tip catheters were associated with a lower procedure cost and shorter time to achieve reperfusion. Similar rates of reperfusion and intracranial hemorrhages were observed in both groups.